2018
DOI: 10.1016/j.mayocp.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relationships Between Weight Change and Sleep Apnea in a Behavioral Weight Loss Intervention

Abstract: Behaviorally induced weight loss in overweight/obese adults was associated with significant AHI reduction. However, the presence of OSA was associated with blunted weight loss, potentially via reduced adherence to behaviors supporting weight loss. These results suggest that OSA screening before attempting weight loss may be helpful to identify who may benefit from additional behavioral counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…As noted in our previous work using these data, a significant percentage of the participants had undiagnosed OSA at baseline [ 19 ]. Separate analyses (not shown) were conducted on the subset of participants with OSA data.…”
Section: Methodssupporting
confidence: 52%
“…As noted in our previous work using these data, a significant percentage of the participants had undiagnosed OSA at baseline [ 19 ]. Separate analyses (not shown) were conducted on the subset of participants with OSA data.…”
Section: Methodssupporting
confidence: 52%
“…In this sample, we previously reported that OSA was associated with worse weight loss in the context of a behavioral weight loss intervention. 25 For these analyses, valid baseline or 6-month AHI data (i.e., ≥2 hours of recording time) were available for 117 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Because OSA is associated with worse sleep 43 and we previously reported that OSA is associated with blunted weight loss, 25 we also explored whether OSA severity accounted for any associations observed between sleep health and weight change. In the subsample with valid AHI data ( n =117), AHI at the beginning of each interval was added as a covariate to the models noted above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective weight loss that is maintained has lasting beneficial effects on energy metabolism, and helps to prevent adverse metabolic and cardiovascular events [91]. Lifestyle modification in patients with OSA and diabetes has multiple benefits including weight reduction and improvements in both severity of OSA and glucose control [92].…”
Section: Treatmentmentioning
confidence: 99%